Optimizing derivatization conditions using an experimental design and simultaneous estimation of artemether and lumefantrine by ratio first order derivative spectrophotometric method. Issue 5 (1st September 2017) - Christian, Jenee; Shah, Purvi; Patel, Margi; Patel, Kalpana; Gandhi, Tejal
Abstract: Artemether–lumefantrine is the most widely used artemisinin-based combination therapy for malaria. The present work aims to develop and validate a simple, accurate, precise and rapid ratio first order derivative spectrophotometric method for the simultaneous estimation of artemether and lumefantrine in a fixed dose combination tablet. The first step in development of the method was to derivatize artemether. As artemether does not show absorption in the UV region, it was derivatized using hydrochloric acid as the derivatizing agent. The derivatizing conditions were further optimized by full factorial multivariate approach, where the independent variables were volume of concentrated hydrochloric acid and time taken for artemether derivatization at room temperature. Furthermore, based on the statistical analysis, derivatizing conditions were optimized i.e. 1.3 ml of conc. HCl at room temperature for 30 min. At this condition, the artemether was found to absorb in the UV region satisfactorily, and the absorbance of lumefantrine was found to remain unaffected. The developed method showed good calibration data in the range of 5–30 μg/ml for artemether and 2–12 μg/ml for lumefantrine. The mean % recovery values were found to be 99.96–100.49% and 99.48–100.31% for artemether and lumefantrine, respectively. Additionally, the developed method was effectively applied in the estimation of artemether and lumefantrine in a commercial tablet (ARH-L DS tablets), suggesting that it can be practically applied for quality control of routinely examined drugs in combined dosage forms with the reduced expenditure of time.